The reparative principles of compulsory taxation in restructuring plans and free competition - Sanjuán y Muñoz, Enrique (2024)
This paper analyzes the rules and principles applicable to restructuring plans from the double perspective of the plans that are imposed through the CCCD (Cross-Class Crawn-Down) rule and those that can be considered consensual insofar as they do not involve an interclass affectation within such plans. It also analyzes the possibility of establishing a system that allows a control of these rules either ex officio or at the request of a party and the effectiveness that can be achieved with one, the other or mixed systems. A defective control or lack of control of these could affect, in the analyzed area, free competition and therefore unduly favor some over others, both in a situation of business crisis and restructuring as well as those that are not in such a situation.